Competitiveness of the Malaysian food processing industry - Ismail, Mohd Mansor; Yusop, Zulkornain (Routledge, 2014)
Competitiveness is the goal sought after by governments and private sectors of many developing countries, including Malaysia. The study used net social profits (NSP) at the production level and the Porter diamond approach at the firms’ level to evaluate the competitiveness of 16 food-processing sectors from 2000 to 2008. The results indicate that processed-food industries have a comparative advantage but at a different magnitude. A time trend was fitted to track the dynamic NSP indices where positive trends indicate improvement in competitiveness. The range of NSP indices is quite wide, from RM 1,707.70 for snacks to RM 35.36 for vegetable and animal oils and fats, reflecting the need to improve resource allocation from low to high comparative advantage sectors. The NSP trend and Porter diamond conditions (demand condition, factor inputs, firm strategy and rivalry, and related supporting industries) suggested that the food processing cluster is gaining competitiveness.